Empire of terror : Iran's Islamic Revolutionary Guard Corps - Silinsky, Mark (Potomac Books, An imprint of the University of Nebraska Press, 2021)
"Iran's Islamic Revolutionary Guard Corps increasingly poses an existential threat to Western security and to Sunni and the few non-Muslim civilizations remaining in the Middle East. Empire of Terror captures this. It will update current academic literature and provide insights gained from the Author's 35 years as an analyst in the U.S. Defense Intelligence Community"--